FEM OF THE THERMAL VARIATION AND STRESS DURING METALDEPOSITION IN RECONDITIONING TECHNOLOGY - Dan Florin NITOI; Gheorghe AMZA; Claudiu BABIS (Fiabilitate şi Durabilitate)
The paper presents the finite element modeling of the temperature behavior and stress mapduring the reconditioning process. This analyze is important to be done because if the temperature of thereconditioned piece is greater than about 2000 C structural transformations could appears. On the other hand,important stress appears at this temperatures. These stress, in some conditions can destroy the integrity of thedeposed metal layer.